Encapsulation of a living bioelectrode by a hydrogel for bioelectrochemical systems in alkaline media1. Issue 23 (21st June 2015) - Chen, Shuiliang; Yang, Fangfang; Li, Chungen; Zheng, Suqing; Zhang, Hua; Li, Ming; Yao, Haimin; Zhao, Feng; Hou, Haoqing
<x xml:space="preserve">Abstract</x> A hydrogel-bioelectrode was fabricated by encapsulating a living electroactive biofilm with a poly(vinyl alcohol) hydrogel through a freezing/thawing process for bioelectrochemical systems in alkaline media.